Glioblastoma-derived Tumor Cells Induce Vasculogenic Mimicry through Flk-1 Protein Activation - Francescone, Ralph (American Society for Biochemistry and Molecular Biology, 2012)
Glioblastoma (GBM) is extremely aggressive and essentially incurable. Its malignancy is characterized by vigorous microvascular proliferations. Recent evidence has shown that tumor cells display the ability to drive blood-perfused vasculogenic mimicry (VM), an alternative microvascular circulation independent of endothelial cell angiogenesis. However, molecular mechanisms underlying this vascular pathogenesis are poorly understood. Here, we found that vascular channels of VM in GBM were composed of mural-like tumor cells that strongly express VEGF receptor 2 (Flk-1). To explore a potential role of Flk-1 in the vasculogenesis, we investigated two glioblastoma cell lines U87 and GSDC, both of which express Flk-1 and exhibit a vascular phenotype on Matrigel. Treatment of both cell lines with either Flk-1 gene knockdown or Flk-1 kinase inhibitor SU1498 abrogated Flk-1 activity and impaired vascular function. Furthermore, inhibition of Flk-1 activity suppressed intracellular signaling cascades, including focal adhesion kinase and mitogen-activated protein kinase ERK1/2. In contrast, blockade of VEGF activity by the neutralizing antibody Bevacizumab failed to recapitulate the impact of SU1498, suggesting that Flk-1-mediated VM is independent of VEGF. Xenotransplantation of SCID/Beige mice with U87 cells and GSDCs gave rise to tumors harboring robust mural cell-associated vascular channels. Flk-1 shRNA restrained VM in tumors and subsequently inhibited tumor development. Collectively, all the data demonstrate a central role of Flk-1 in the formation of VM in GBM. This study has shed light on molecular mechanisms mediating tumor aggressiveness and also provided a therapeutic target for patient treatment.